Pacifism or Anti-Imperialism?: The CCF Response to the Outbreak of World War II - Naylor, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1997)
AbstractExamining the Co-operative Commonwealth Federation's response to the outbreak of World War II, this paper shifts the focus away from J.S. Woodsworth's allegedly “pacifist” refusal to support the war effort. Instead, it explores the context and language of the broader debate among CCFers regarding militarism, fascism and imperialism. Very rarely was this debate framed in pacifist terms. It was axiomatic to the CCF that the twin evils of fascism and war were the products of capitalism and that war among capitalist powers retained an imperialist character. Acquiescing to participation in such a war was not only unprincipled but also undermined the basis upon which a socialist, working-class identity could be constructed. Once the war was under way, the CCF could hardly deny its initial ambivalence to the war, but chose to restate it in pacifist terms that were less challenging to the Canadian state, the allies, and the war effort.